2021
DOI: 10.21037/jgo-20-338
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of the combination of nano-liposomal irinotecan and 5-fluorouracil/leucovorin in advanced pancreatic adenocarcinoma: post-approval clinic experience

Abstract: Background: Nano-liposomal irinotecan (nal-IRI) plus 5-fluorouracil/leucovorin (5-FU/LV) is the regimen of choice in the 2 nd line setting for advanced pancreatic adenocarcinoma (PAC). However, realworld data is limited. Our objectives were to elicit the real-word effectiveness and safety of this combination as an advanced line of therapy in pancreatic cancer patients and analyze the impact of prior lines of therapy on survival outcomes with this regimen. Methods: We conducted a retrospective cohort study of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 26 publications
(44 reference statements)
10
27
0
Order By: Relevance
“…The NAPOLI-1 study and real-world analyses had confirmed that nal-IRI+5-Fu/LV is an effective chemotherapeutic regimen in patients with mPDAC after gemcitabine-based treatment. 7,[9][10][11][12][13][14][15][16][17] As gemcitabine-based and FOLFIRINOX regimens are both established first-line treatments for mPDAC, nal-IRI+5-FU/LV is often utilized as the second-line or third-line treatment for metastatic pancreatic cancer depending on the previously prescribed chemotherapeutic agents. As a result, patients who received nal-IRI+5-FU/LV in a later treatment line inevitably have poor survival outcomes as opposed to those receiving the same treatment in an earlier treatment line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The NAPOLI-1 study and real-world analyses had confirmed that nal-IRI+5-Fu/LV is an effective chemotherapeutic regimen in patients with mPDAC after gemcitabine-based treatment. 7,[9][10][11][12][13][14][15][16][17] As gemcitabine-based and FOLFIRINOX regimens are both established first-line treatments for mPDAC, nal-IRI+5-FU/LV is often utilized as the second-line or third-line treatment for metastatic pancreatic cancer depending on the previously prescribed chemotherapeutic agents. As a result, patients who received nal-IRI+5-FU/LV in a later treatment line inevitably have poor survival outcomes as opposed to those receiving the same treatment in an earlier treatment line.…”
Section: Discussionmentioning
confidence: 99%
“…Recent real-world studies have reported a poor survival outcome of nal-IRI+5-FU/LV therapy in mPDAC patients previously treated with conventional irinotecan therapy. [10][11][12] Limited by the small number of patients, all of these studies used univariate analysis to evaluate the effect of conventional irinotecan treatment on nal-IRI+5-FU/LV therapy. [10][11][12] As a result, these results have been criticized for the heterogeneity of patient F I G U R E 3 Overall survival (A) and time-to-treatment failure (B) according to previous conventional irinotecan treatment or non-treatment after propensity score matching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Several real-world studies have reported similar results, demonstrating that previous irinotecan treatment was a poor prognostic variable for patients receiving nal-IRI treatment. [17][18][19][20] The same concept applies to patients with previous exposure to 5-FU, which might also compromise the efficacy of nal-IRI + 5-FU/LV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…15 Several studies have reported real-world data on the clinical efficacy and toxicity of nal-IRI + 5-FU/LV in comparable settings. 1623 These published studies have reported the common practice of pre-emptive nal-IRI dose reduction to achieve better tolerability and safety profiles without compromising treatment efficacy. 20,21 However, these studies were limited by a single institute experience and small numbers of patients.…”
Section: Introductionmentioning
confidence: 99%